How financial performance and state-owned enterprise (SOE) values are affected by good corporate governance and intellectual capital perspectives - Yustinus Budi Hermanto; Lusy Lusy; Maria Widyastuti (Economies, 2021)
The implementation of good governance and attention to resources will affect company survival. The purpose of this study was to examine the effect of good corporate governance and intellectual capital on financial performance and company value through statistical and econometrical tests on SOEs in Indonesia. This is quantitative research with state-owned enterprises (SOEs) listed on the Indonesia Stock Exchange. The total study population was 16 SOEs. This study used a saturated sample. Furthermore, the exogenous variables in this study were good corporate governance (GCG) and intellectual capital, whereas the endogenous variables were the company and financial performance. This study used the statistical analysis inferential because the variables used indicators and were formative. The results indicated that GCG and financial performance have positive effects on firm value, intellectual capital does not affect company value, and GCG and intellectual capital have positive effects on financial performance. The evaluation of indirect effects in this study showed that financial performance mediates the effect of intellectual capital and GCG on company value.
Keywords: 330; company value; financial performance; good corporate governance (GCG); intellectual capital